Functional annotation of melanoma risk loci identifies novel susceptibility genes. (21st October 2019) - Fang, Shenying; Lu, Jiachun; Zhou, Xinke; Wang, Yuling; Ross, Merrick I; Gershenwald, Jeffrey E; Cormier, Janice N; Wargo, Jennifer; Sui, Dawen; Amos, Christopher I; Lee, Jeffrey E
Abstract: Genome-wide association study (GWAS)-identified single-nucleotide polymorphisms (SNPs) are tag SNPs located in both transcribed and non-coding regulatory DNA regions, rather than representing causal or functional variants for disease. To identify functional variants or genes for melanoma susceptibility, we used functional mapping and annotation (FUMA) to perform functional annotation of the summary statistics of 2541 significant melanoma risk SNPs ( P < 5 × 10 −8 ) identified by GWAS. The original GWAS melanoma study included 15 990 cases and 26 409 controls, representing the largest international meta-analysis of melanoma susceptibility. We prioritized 330 unique genes, including those in immune cytokine signaling pathways, from 19 loci through positional, expression quantitative trait locus, and chromatin interaction mapping. In comparison, only 38 melanoma-related genes were identified in the original meta-analysis. In addition to the well-known melanoma susceptibility genes confirmed in the meta-analysis ( MC1R, CDKN2A, TERT, OCA2 and ARNT/SETDB1 ), we also identified additional novel genes using FUMA to map SNPs to genes. Through chromatin interaction mapping, we prioritized IFNA7, IFNA10, IFNA16, IFNA17, IFNA14, IFNA6, IFNA21, IFNA4, IFNE and IFNA5 ; these 10 most significant genes are all involved in immune system and cytokine signaling pathways. In the gene analysis, we identified 72 genes with a P < 2.5 × 10 −6 . The genes associated with melanoma risk were DEF8 ( P = 1.09 × 10 −57 ), DBNDD1 ( P = 2.19 × 10 −42 ), SPATA33 ( P = 3.54 × 10 −38 ) and MC1R ( P = 1.04 × 10 −36 ). In summary, this study identifies novel putative melanoma susceptibility genes and provides a guide for further experimental validation of functional variants and disease-related genes. Abstract : Two thousand five hundred and forty-one significant melanoma single-nucleotide polymorphisms with functional annotation were mapped to genes using the bioinformatics tool functional mapping and annotation. We identified novel melanoma susceptibility genes involved in immune and cytokine signaling pathways, and DEF8, DBNDD1, SPATA33 .